A cross-sectional study on the quality of life in HIV infected goldminers on highly active antiretroviral therapy in an industrial setting in South Africa - Mngadi, Kathryn Therese (Department of Public Health and Family Medicine, 2014)
Includes bibliographical references (leaves 70-75).